Blood pressure in different ethnic groups (BP-Eth): a mixed methods study. Issue 6 (5th November 2012) - Wood, Sally; Martin, Una; Gill, Paramjit; Greenfield, Sheila M; Haque, M Sayeed; Mant, Jonathan; Mohammed, Mohammed A; Heer, Gurdip; Johal, Amanpreet; Kaur, Ramandeep; Schwartz, Claire; McManus, Richard J
Abstract : Introduction: People of South Asian, African-Caribbean and Irish ethnicity are known to have worse cardiovascular outcomes than those from the white British group. While the reasons underpinning this are complex, the effect of hypertension is both significant and modifiable. In recent years, there has been increasing interest in and uptake of 'out-of-office' methods for blood pressure (BP) monitoring. However, guidance in this area has been largely based on research among the white population. This study aims to answer the following questions: (1) How often and in what ways does blood pressure (BP) monitoring occur and how does this differ between white and the above minority ethnic populations. (2) Are the thresholds for diagnosis of hypertension, and treatment targets in hypertension comparable for white British and minority ethnic populations using different measurement modalities: office blood pressure, ambulatory BP monitoring and home monitoring? (3) What preferences for BP measurement do people from white and minority ethnic populations have? Methods and analysis: A mixed methods approach will be used including the following: (1) A postal survey sent to 8000 hypertensive and not-known-to-be-hypertensive people from all four ethnic groups will determine current patterns of BP monitoring. (2) A validation study will compare BP measurement by ambulatory monitoring with office standard measurement, office research measurement and home monitoring in 200 people from each of the ethnic groups concerned. (3) Focus groups organised by ethnicity and gender will gather qualitative data regarding patient preferences for and experiences of BP measurement in each of the given modalities. The data collected from these phases will be analysed appropriately in order to answer the above research questions. Ethics and dissemination: Ethical approval has been gained from the Black Country Research Ethics Committee: Ref 09/H1202/114. The results of this work will be disseminated via journal publication and conference presentation.